DESIGN INVESTIGATION ON FOOT DEFORMITIES WORKING FOOTWEAR - Nor Rofizah Johari; Khatijah Md Saad (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
Footwear was planned to protect the feet from the environment. Choosing the right footwear based on foot conditions and requirements enabling to reduce the risk of injury, fast fatigue, and foot pains. Good footwear should provide stability to the joints of the foot and a foundation upon which the foot can function. The objective of this study is to provide information that will assist researchers and designers in identifying, designing and offering appropriate and better working footwear designs for those with foot deformities. Two identified workers from the footwear factory with congenital foot deformities participated in this prospective intervention study for over 12 months. An interview and a video on how the participant wears and walk with normal commercial shoes were recorded. The physical examination was also assessed including the footwear, feet, legs, and hips of the subjects. They were examined with a focus on the areas of deformities. Each leg has different shape and concerns. Hence, each footwear designed for those with foot deformities must be customized base on the factors of type of deformities, body size and the remaining skeletal structure and muscular. With proper modification, people who have foot deformities and unable to buy suitable footwear will be able to relieve the pain and at the same time increase the individual motivation in job satisfaction, motivation or enthusiasm to work and reducing levels of stress or emotional upset.